Identidade da organização-cidade de Curitiba: estudo histórico da primeira gestão de Jaime Lerner - Morgado, Ubirajara (2016)
This study aimed to understand the formation of collective identity in a city as organization like Curitiba, focused on the analysis of municipal management from 1971 to 1975. The text was constructed from the theoretical review of the organizational identity issue, which stood out the principles stipulated by Albert and Whetten: centrality, distinctiveness and continuity. In addition to this conceptual guidance, we seek to revisit the concept of a city as organization, treated by MacAllister, Fischer, Saraiva and Carrieri. Methodologically, we seek to guide the documentary historical research in the microfilm archives of the Gazeta do Povo that are under the custody of the Public Library of Paraná (BPP), the Institute Jaime Lerner files (IJL) dealing with the personal collection of this ruling and sources literature about local history. Therefore, our study was formed from two stages, the historical reconstruction of municipal management 1971-1975 and analysis of aspects that revealed the pillars of centrality, distinctiveness and durability in the context of city as organization. We conclude that the municipal administration of 1971-1975 played a key role in the formation of identity elements of the organization, the city of Curitiba, especially as regards the idea of avantgarde and modernity as well as the city-model and great quality life. One of the key aspects was the guidance for urban planning that existed back the Agache plan, as well as the positive dialogue with the media.